714 Effects of direct irradiation on cardiac implantable electronic devices. (8th December 2021) - Mitacchione, Gianfranco; Arabia, Gianmarco; Bontempi, Luca; Cerini, Manuel; Salghetti, Francesca; Milidoni, Antonino; Ahmed, Ashraf; Bognoni, Ludovica; Aboelhassan, Mohamed; Curnis, Antonio
Abstract: Aims: Cardiac implantable electronic devices (CIEDs) may sustain damages during a course of radiation therapy, especially when the beam is directed onto the pulse generator, with device electrical reset and/or sudden battery drain. 2010 HRS/ASA expert consensus, and all CIEDs manufacturers, recommend to avoid devices direct irradiation with an accumulated dose that exceed five grays (Gy). In our prospective study, we tested the effects of direct irradiation on CIEDs with different radiation doses, also higher than 5 Gy. Methods and results: Thirty-seven CIEDs of Medtronic, Abbott, Biotronik, and Boston Scientific were collected during system upgrading or lead extraction procedures. All devices were considered if they had at least 80% of residual battery capacity. All CIEDs were programmed with same default electrical parameters. Depending by CIED type, pacing mode was configured in VVI, VVIR, VDDR, or DDDR, and biventricular stimulation was activated, if present. ICDs electrical therapies were set-up with a pre-determined configuration. All devices were singularly placed in a 30 cm × 30 cm plastic bowl containing 2 l of deionized water that was placed over 5 cm Rockwool to simulate the backscatter and irradiated by a linear accelerator (Elekta Synergy ® ). CIEDs were divided into two groups depending on irradiation dose delivered: 5 Gy and 10 Gy. No significant differences in battery drainage were observed after irradiation respect to baseline in 5 Gy as well 10 Gy group [7.9 ± 3.1 vs. 7.5 ± 2.1 (years) battery longevity, P = 0.693; 7.7 ± 3.1 vs. 7.4 ± 2.1 (years) battery longevity, P = 0.677, respectively) (Figure). Moreover, all CIEDS saved the baseline program setting, without device reset events (Table). Conclusions: Our data confirm that CIEDs direct irradiation of 5 Gy is safe, of note, direct irradiation up to 10 Gy seems to be similarly safe concerning the risk of CIEDs electrical reset and/or unexpected battery drain.